Socio Religious Settings and the Development of Accounting in Indonesia - Rizal Yaya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
During 1980’s, culture has featured in the discussion on the factors influencing the development of accounting. On the other hands, religion has an important role in shaping a culture as it also produces social understanding, values, beliefs and symbols, which can be absorbed by a society and reproduced as a culture of the society. This implies that the influence of religion on accounting is possibly occurred. This research tries to show how such influence occurred along with the development of religions in Indonesia. It is argued that different socio religious settings would result in different way of development of accounting. To support the argument, an empirical test would be conducted on (1) the perception of Muslim accounting academician in Yogyakarta on the appropriateness of conventional acounting for Muslim users, and (2) the impact of different religious settings on the perception of Muslim accounting academicians on the suitability of conventional accounting in achieving Islamic socio economic objectives. This test is on the perception of Muslim accounting academician on the appropriateness of conventional accounting for Muslim users will conducted by using one sample t-test. Meanwhile thethe impact of different religious settings will be analzed by using analysis of variance (ANOVA) test.